The Effect of History of Low Birth Weight in Newborns and Maternal Anemia in Pregnancy on the Risk of Stunting in Toddlers Age 0-24 Months in Tanjung Bintang Health Center South Lampung Regency - Dian Isti Angraini; Kristian Pieri Ginting; Efriyan Imantika (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Stunting is the condition in children when their height is shorter than a child of his age because of stunted growth due to chronic malnutrition. Stunting can be caused by low birth weight in newborns and maternal anemia. The objective of the study is to know the effect of low birth weight in newborns and maternal anemia on the risk of stunting in the toddler with the age range between 0-24 months in the Tanjung Bintang Primary Health Care. This research is an observational-analytic study with a cross-sectional approach. This research was conducted in the region of Tanjung Bintang Primary Health Care. The sample was 73 toddlers with an age range between 0-24 months. Data were analyzed with a Chi-square test to know the influence of the independent variable with a value of α = 0,05. The results found a 37% risk of stunting, 12.3% history of low birth weight in newborns, and 34.2% history of maternal anemia. The results of the bivariate analysis was no influence of a history of low birth weight in newborns on the risk of stunting (p-value = 0.718) and there was an influence of maternal anemia on the risk of stunting in toddlers (p-value = 0.001). There is no influence history of low birth weight in newborns on the risk of stunting and there is an influence of maternal anemia on the risk of stunting in toddlers aged range between 0-24 months in the region of Tanjung Bintang Primary Health Care.